2016
DOI: 10.1002/anie.201510938
|View full text |Cite
|
Sign up to set email alerts
|

CLIP‐COSY: A Clean In‐Phase Experiment for the Rapid Acquisition of COSY‐type Correlations

Abstract: The COSY experiment is an essential homonuclear 2D NMR experiment for the assignment of resonances. Its multiplet line shape, however, is often overly complicated, potentially leads to signal intensity losses, and is responsible for long minimum overall acquisition times. Herein, we present CLIP-COSY, a COSY-type experiment yielding clean in-phase peaks. It can be recorded within a few minutes and benefits from enhanced signal intensities for most cross-peaks. In combination with non-uniform sampling, the expe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
38
0
1

Year Published

2017
2017
2021
2021

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 52 publications
(41 citation statements)
references
References 50 publications
1
38
0
1
Order By: Relevance
“…Some attractive options for the routine characterisation of small molecules are presented in Figure . These incorporate not only the commonly employed 2D homonuclear correlation elements such as TOCSY, NOESY, and ROESY but also the recently proposed CLIP‐COSY (clean in‐phase COSY) that provides for high‐resolution phase‐sensitive COSY presentation and the classic double‐quantum filtered COSY (DQF‐COSY).…”
Section: Resultsmentioning
confidence: 99%
“…Some attractive options for the routine characterisation of small molecules are presented in Figure . These incorporate not only the commonly employed 2D homonuclear correlation elements such as TOCSY, NOESY, and ROESY but also the recently proposed CLIP‐COSY (clean in‐phase COSY) that provides for high‐resolution phase‐sensitive COSY presentation and the classic double‐quantum filtered COSY (DQF‐COSY).…”
Section: Resultsmentioning
confidence: 99%
“…However, for molecules that exhibit broad multiplets, these methods suffer because of the antiphase components present in the F 1 / F 2 dimensions or involve longer refocusing periods, thereby considerably reduce the signal sensitivity and make the measurements difficult. In this regard, the subsequent advanced versions of COSY: (a) constant‐time (CT) COSY with gradient z‐filter, called in‐phase COSY (IP‐COSY) reported by Xia et al, and (b) clean in‐phase COSY (CLIP‐COSY) by Koos et al, has shown great potential. The IP‐COSY generates fairly strong in‐phase signals in both the dimensions, but the resolution in the indirect dimension is limited by the CT evolution.…”
Section: Methodsmentioning
confidence: 99%
“…The initial part of the PS‐IPZF‐COSY sequence uses the constant‐time (CT) t 1 evolution followed by adiabatic chirp‐shaped inversion pulses during the spatial encoding gradient (G4), which suppress the zero‐quantum magnetization with the aid of Keeler's z‐filter . In the case of PS‐CLIP‐COSY, the initial part of pulse scheme uses a perfect echo‐based in‐phase block flanked by adiabatic z‐filters, as described in the original CLIP‐COSY publication . The coupling time delay (Δ) has been optimized as follows.…”
Section: Methodsmentioning
confidence: 99%
“…But in some cases, the true measure of the quality of a spectrum depends on the ratio between the level of the signals and the artifacts. An example is provided by the F1‐decoupled CLIP‐COSY experiment . The spectra it produces are quite powerful to analyze complex mixtures of compounds such as of carbohydrates because they eliminate scalar coupling structures in the vertical F1 dimension (see Figure ).…”
Section: Analysis Of Spectral Artifactsmentioning
confidence: 99%